Global Perspectives on Archaeological Field Schools Constructions of Knowledge and Experience - Mytum, Harold; SpringerLink (Online service) (New York, NY : Springer New York, 2012)
Archaeological field schools, notably in North America but also across the world, are seminal student experiences. They are also important vehicles by which research students and academic staff carry out fieldwork research, often away from the environs of their home institution. Field schools are teaching and research projects, but they also take place within a contemporary local context. Global Perspectives on Archaeological Field Schools: Constructions of Knowledge and Experience is the first ever collection of studies examining the tensions between teaching, research and local socio-cultural conditions, and explores the range of experiences associated with field schools. It will be of interest to all those wishing to attend a field school, whether as student or junior staff member, and for novice and experienced field school directors who can gain fresh insights from others$1 (Bexperiences.s
Theory and Practice.-Introduction by Harold Mytum.-The Pedagogic Value of Field Schools: Some Basic Concepts by Harold Mytum.-Field Schools, Transferrable Skills and Enhancing Employability by Hannah Cobb and Karina Croucher -- Archaeology for All? Inclusive policies for Field Schools by Amanda Clarke and Tim Phillips.-Archaeological Field Schools and Fieldwork Practice in an Australian Context by Sarah Colley.-The UCLA Archaeology Field Schools Program: Global Reach, Local Focus by Ran Boytner.-Teaching and Researching.-Two-centre Field Schools: Combining Survey and Excavation in Ireland and Wales or the Isle of Man. by Harold Mytum -- Constructing New Knowledge in Industrial Archaeology by Timothy James Scarlett and Sam R. Sweitz.-Underwater.-The University of West Florida$1 (Bs Maritime Field School Experience by John R. Bratten.-Freshwater Underwater Archaeology Field School, Good Practice, Good Science by Anne Corscadden Knox and Sheli O Smith.-Non-Excavation.-Pompeii Food and Drink Project by Betty Jo Mayeske, Robert I. Curtis and Benedict Lowe.-Historical Archaeology Artifact Training in Field Schools: Three International Case Studies by Alasdair Brooks.-Fieldwork and People -- From Graduate to Professor: Changing Perspectives on Field Schools by Bonnie J. Clark.-Suvoyuki Means Joint Effort: Archaeologists, the Hopi Tribe, and the Public at Homol$1 (Bovi by Lisa C. Young.-Field Schools: people, places and things in the present by Harold Mytum.s
Keywords: Social sciences; Environmental management; Archaeology; Social Sciences; Archaeology; Environmental Management